Editorial: Molecular advances and applications of machine learning in understanding autism and comorbid psychiatric disorders - Salam Salloum-Asfar (656363) (2023)
This editorial encapsulates 15 meticulously curated articles, contributing to the profound exploration of neurodevelopmental disorders (NDDs), with a distinct focus on autism spectrum disorder (ASD) and its intricate interplay with comorbid psychiatric conditions. The contributions cast light on the intricate etiology and molecular mechanisms underlying these complex disorders. This Research Topic examines myriad dimensions, encompassing various facets, such as genetic predisposition, dynamic gene expression, signal transduction pathways, compensatory mechanisms, and neural network organization. Other Information Published in: Frontiers in Molecular Neuroscience License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fnmol.2023.1277814